ENHANCING STUDENT ENGAGEMENT AND CRITICAL THINKING THROUGH DIRECT COMMUNICATIVE LANGUAGE TEACHING: AN EMPIRICAL STUDY IN TERTIARY EFL CONTEXT - Masrurotul Ajiza; Feny Arafah (Universitas Wiralodra, 2026)
This study explores the impact of Direct Communicative Language Teaching (CLT) on student engagement and critical thinking in an English for Specific Purposes (ESP) classroom. It aims to answer three questions: (1) How is Direct CLT implemented? (2) In what ways does CLT influence students’ behavioural, emotional, and cognitive engagement during English lessons? and (3) How do CLT-based activities develop students’ critical thinking in classroom interactions? Conducted with 1 English lecturer and 15 undergraduate Geodetic Engineering students of Institut Teknologi Nasional (ITN) Malang, this qualitative study collected data through classroom observations and student questionnaires combining Likert-scale and open-ended items. The findings reveal that Direct CLT shifted the classroom dynamic from a teacher-centered to a student-centered environment, where learners actively participated, collaborated, and communicated meaningfully. Students demonstrated behavioural engagement through teamwork, emotional engagement through enjoyment and positive interaction, and cognitive engagement. The use of authentic, discipline-related tasks enabled students to link English learning with real-world communication and professional relevance. Overall, the findings indicate that Direct CLT effectively enhances communicative competence, critical thinking, and collaboration among engineering students, suggesting that ESP instruction should integrate communicative and contextualized pedagogies to better prepare learners for authentic professional communication.